SCIENTIFIC EXPLANATION OF COMPOSITION OF ACIDOPHILIC-WHEY ICE CREAM, ENRICHED WITH PROTEIN - Galina POLISCHUK (Stefan cel Mare University of Suceava, 2021)
The work is devoted to solving the actual problem of the dairy industry - complex processing of food raw materials, expanding the range of dairy and milk-containing products of high nutritional value due to enrichment of protein, pro- and prebiotics, rational use of production resources by reducing the the technological process duration. The aim of the research is to substantiate the composition of a new type of acidophilic-whey ice cream of high nutritional value due to enrichment with a complex of proteins, probiotic sourdough and pectin-containing vegetable paste. The main tasks of scientific work are: development of a scientifically based formulation for a new type of ice cream to expand the range of products that will improve the nutrition structure of the Ukraine`s population. The methods used to study the organoleptic and physico-chemical indicators of blends and ice cream are well known and presented in the article. The method of production of sour milk ice cream and the choice of dairy raw materials for obtaining a fermented base was theoretically substantiated, the functional and technological properties of protein concentrates and their compositions in ice cream formulations were studied, the rational content of protein in ice cream was established, also the expediency of using pectin-containing vegetable paste in acidophilic-whey ice cream was proved.